The Capitalist Machine: Computerization, Workers' Power, and the Decline in Labor's Share within U.S. Industries. (June 2013) - Kristal, Tali
This article addresses an important trend in contemporary income inequality—a decline in labor's share of national income and a rise in capitalists' profits share. Since the late 1970s, labor's share declined by 6 percent across the U.S. private sector. As I will show, this overall decline was due to a large decline (5 to 14 percent) in construction, manufacturing, and transportation combined with an increase, albeit small (2 to 5 percent), in labor's share within finance and services industries. To explain the overall decline and the diverse trends across industries, I argue that the main factor leading to the decline in labor's share was the erosion in workers' positional power, and this erosion was partly an outcome of class-biased technological change, namely computerization that favored employers over most employees. I combine data from several sources to test for the independent effects of workers' positional power indicators (i.e., unionization, capital concentration, import penetration, and unemployment) and the direct and indirect effects of computer technology on changes in labor's share within 43 nonagricultural private industries and 451 manufacturing industries between 1969 and 2007. Results from error correction models with fixed-effect estimators support the study's arguments.